OBSERVATIONS ON THE FISHERIES OF MULLET AND SCOPE FOR ITS CULTURE IN GULF OF KUTCH - Chhaya, N D; Buch, A U; Narayanan, K R (Indian Journal of Fisheries, 2011)
Fisheries of mullets, gear and tackle used, and scope for mullet culture in the Gulf of Kutch are discussed.